First report of Antigastra catalaunalis on sesame in Greece - Simoglou, K. B.; Anastasiades, A. I.; Baixeras, J.; Roditakis, E. (ENTOMOLOGIA HELLENICA, 2017)
In August 2016, severe infestations of sesame crops by the sesame leaf webber and capsule borer, Antigastra catalaunalis (Duponchel) (Lepidoptera: Crambidae), were recorded in rural areas of the Regional Unit of Drama, Northern Greece. Larval feeding-damage symptoms were observed on leaves and capsules. Infestations were recorded in all of the inspected sesame fields. The infestation levels were considerable high resulting in significant economic loss. To our knowledge, this is the first report of A. catalaunalis severe infestation on sesame in Greece.